Время в антиутопическом дискурсе (на материале украинской и русской прозы конца ХХ – начала ХХІ веков - Лавринович, Лилия Богдановна; Lavrynovych, Liliia B.; Лавринович, Лілія Богданівна (Елецкий государственный университет имени И. А. Бунина, 2014)
В статье речь идет о художественном времени руской и украинской антиутопии рубежа ХХ–ХХІ вв. На примере романов В. Лобова «Дом, который сумасшедший», Д. Глуховского «Будущее», Т. Антиповича «Хронос», Т. Толстой «Кысь», М. и С. Дяченко «Армагед-дом», А. Ирванца «Ривнэ / Ровно / Стена. Якобы роман» и В. Сорокина «День опричника» анализируется образ времени в произведениях (прежде всего время антиутопического мира и субъективное психологическое время героя-рассказчика), также поэтика времени как составляющая поэтики произведения в целом.

This article is about artistic time of Russian and Ukrainian anti-utopia in the end of 20th and at the beginning of 21th centuries. The artistic images of time are analyzed in such novels as V. Lobov «The house, which is mad», D. Gluhovskiy «The future», T. Antipovich «Khronos», T. Tolstaya «Kysj», M. and S. Dyachenko «Armaged-house», A. Irvanetsj «Rivne / Rowno / Wall. As if the novel» and V. Sorokin «The day of oprichnik». First of all the time of the anti-utopian world and subjective psychological time of hero-teller are analyzed. Also the poetics of time as constituent of poetics of work on the whole is studied.
Time in the anti-utopian diskourse (on the material of ukrainian and russian prose in the end of 20th and at the beginning of 21th centuries)
Keywords: антиутопия; мифологическое время; темпоральная картина действительности; модусы времени; anti-utopia; mythological time; temporal picture of reality; moduses of time